Wizards in school - Mora, Amelia, 1980-; Snchez, Ana C.; Levy, Dana Guterman (Kansas City, Missouri : Andrews McMeel Publishing, 2024)
"The Tanaka triplets can do magic. The only catch? Their powers must be kept secret. So, obviously, they would never, ever do anything to threaten that ... right?! Triplets Hiro, Akira, and Naoki Tanaka love their school and classmates, but they have one big secret theyre keeping. They can do magic! They learn from their father, and they have one major rule: No magic without permission, no exceptions. Otherwise, theyll have to leave their normal school with all their friends to study how to do magic "the right way ometimes magic feels like the only way to solve a problem! And when they get themselves into all sorts of trouble, its up to the siblings to fix the spells and clean up any magical messes before their parents or a nosy classmate can catch wind of it. This is the first book in a new series thats about fitting in, finding yourself, and problem-solving"--
"Original title: Sayonara Magic 1: Magos en el colegio"-- Colophon.
In English, translated from the Spanish.
Keywords: Magic -- Juvenile fiction; Ability -- Juvenile fiction; Triplets -- Juvenile fiction; Siblings -- Juvenile fiction; Schools -- Juvenile fiction; Wizards -- Juvenile fiction; Secrecy -- Fiction; Problem solving -- Juvenile fiction; Magic -- Fiction; Ability -- Fiction; Triplets -- Fiction; Siblings -- Fiction; Schools -- Fiction; Wizards -- Fiction; Secrecy -- Fiction; Problem solving -- Fiction; Fantasy fiction; School fiction; Humorous fiction